2019
DOI: 10.2147/jpr.s212205
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multidisciplinary pain management program for patients with chronic musculoskeletal pain in Japan: a cohort study</p>

Abstract: IntroductionMultidisciplinary pain management is a useful method for treating chronic musculoskeletal pain. Currently, few facilities in Japan offer multidisciplinary pain treatment, especially in the inpatient setting. We implemented a multidisciplinary pain management program based on International Association for the Study of Pain recommendations. This study described our initial efforts in implementing the program, and reported 3- and 6-month follow-up results.Materials and methodsOur pain management team … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Participants in these studies had reported chronic pain originating from the musculoskeletal systems (knee, spine, joint, back), neurological system (headache and migraine) and unspecified chronic pain. Pain measurement tools used in these studies were the Chronic Pain Grade Scale (CPGS), 18,28 Numeric Pain Rating Scale (NPRS), 15,26 Western Ontario and McMaster Universities osteoarthritis index (WOMAC), 16,17 Brief Pain Inventory (BPI), [23][24][25] pharmacotherapeutic pain inventory, 20 and the Pain, Enjoyment of Life and General Activity score (PEG). 27 3.2 | Quality of studies…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants in these studies had reported chronic pain originating from the musculoskeletal systems (knee, spine, joint, back), neurological system (headache and migraine) and unspecified chronic pain. Pain measurement tools used in these studies were the Chronic Pain Grade Scale (CPGS), 18,28 Numeric Pain Rating Scale (NPRS), 15,26 Western Ontario and McMaster Universities osteoarthritis index (WOMAC), 16,17 Brief Pain Inventory (BPI), [23][24][25] pharmacotherapeutic pain inventory, 20 and the Pain, Enjoyment of Life and General Activity score (PEG). 27 3.2 | Quality of studies…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the studies were judged to be of average quality. Two of the studies were judged to have a serious risk of bias, 21,26 five moderate, [22][23][24][25]27 and only one low risk of bias. 28 The studies were judged to have a serious risk of bias due to participant selection and confounding (Table S2).…”
Section: Observational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of therapy for patients with chronic pain is to improve functional capability while decreasing the level of pain. 4,5 Health professionals are reluctant to prescribe opioids due to stigma with addiction and side effects. 6 There is widespread fear of drug dependency when the painful crisis is managed with opioids.…”
Section: Introductionmentioning
confidence: 99%